Blends of PP/PE co-octene for modified atmosphere packaging applications - Acosta, Mariela Natalia (2011)
The aim of this work was to obtain films of polypropylene (PP)/polyethylene co-octene (POE) blends and study the influence of their composition and mixing conditions on final morphology and ultimate properties (thermal, mechanical, oxygen and water vapour transmission rates). Scanning electron microscopy showed segregation of POE domains in the PP matrix. Thermal analysis indicated that the addition of POE modified neither the melting temperature nor the crystallinity of PP in the pressed films. It was found that permeabilities of films were mainly related to POE content rather than morphological features. For the maximum POE concentration used (40%), the oxygen permeability increased up to μ100% from that of neat PP. A similar trend was found for water vapour permeability. Rigidity of blends dropped significantly with the addition of POE although their ductility slightly increased when compared to pure PP. No significant effect of blend preparation conditions on these properties was found. Mechanical and permeability characteristics of films make them very attractive to be used for MAP of fresh produce such as apple, blueberry and mushroom.